Associations between child disciplinary practices and bullying behavior in adolescents - Graziela A.H. Zottis; Giovanni A. Salum; Luciano R. Isolan; Gisele G. Manfro; Elizeth Heldt (Elsevier, 2014)
OBJECTIVE: to investigate associations between different types of child disciplinary practices and children and adolescents' bullying behavior in a Brazilian sample. METHODS: cross-sectional study, with a school-based sample of 10-to 15-year-old children and adolescents. Child disciplinary practices were assessed using two main subtypes: power-assertive and punitive (psychological aggression, corporal punishment, deprivation of privileges, and penalty tasks) and inductive (explaining, rewarding, and monitoring). A modified version of the Olweus Bully Victim Questionnaire was used to measure the frequency of bullying. RESULTS: 247 children and adolescents were evaluated and 98 (39.7%) were classified as bullies. Power-assertive and punitive discipline by either mother or father was associated with bullying perpetration by their children. Mothers who mostly used this type of discipline were 4.36 (95% CI: 1.87-10.16; p < 0.001) times more likely of having a bully child. Psychological aggression and mild forms of corporal punishment presented the highest odds ratios. Overall inductive discipline was not associated with bullying. CONCLUSIONS: bullying was associated to parents' assertive and punitive discipline. Finding different ways of disciplining children and adolescents might decrease bullying behavior.